Revolution and Exemplarity. The Problem of the Idea and its Realization. Between Kant and Arendt - Bruna Castro, Carolina (Res Publica. Revista de Historia de las Ideas Políticas, 2018)
This paper attempts an approach in a critic way on the relationship between Hannah Arendt and Kant. To accomplish this I considered particularly two books of Arendt; On the revolution and The Life of the Mind. Considering these books I analyze the concepts of revolution, exemplarity, new beginning and Will in their variance with the original proposal of Kant.
Keywords: Arendt; Kant; revolution; exemplarity; will; new beginning